NILAI-NILAI KEHIDUPAN DALAM PUISI AL-MUTANABBI - Nurain Nurain (Sunan Kalijaga State Islamic University Yogyakarta, 2014)
This study assumes that literary works are not neutral or value-free works. Poetry which is the main object of this article carries not only aesthetic values but also personal and social life values, either directly attributed consciously by the poet him/herself or by the audiences. Poetry is one of the main ways to express feeling and imagination among the Arabs since the era of jahiliy (the days of ignorance). Therefore, a poet was highly hallowed and respected like a priest, spokesman, tribal chief, or even prophet. This phenomenon reached its peak in the Abbasid period due to the caliphs’ support. One of the great poets in the Abbasid period was Al-Mutanabbi. This paper examines his poems with the purpose to explore their literary values as well as their various life values using a pragmatic approach. From this study, the writer discovers a number of values, such as intellectual, religious, social, patriotic or heroic, and philosophical, in addition to the poetic aesthetic values in his works. These values are not free from the dynamics of Al-Mutanabbi’s life and his association as a court poet, mainly of Saif al-Daulah’s.